A taxonomic review of the grassland leafhopper genus Aconurella Ribaut (Hemiptera: Cicadellidae: Deltocephalinae: Chiasmini) from China with the description of two new species - Duan, Yani; Zhang, Yalin (Zootaxa, 2012)
Six species of the genus Aconurella Ribaut from China are reviewed including two new records and two new species; de-scriptions and illustrations of these species are provided. Two new species A. furcata sp. n. and A. paradiplachnis sp. n.are described. A key to males of the Chinese species in the genus is also given. A. orientalis is considered a junior synonym of A. prolixa syn. n. and A. solana is considered a junior synonym of A. montana syn. n.